2021
DOI: 10.3390/agronomy11061162
|View full text |Cite
|
Sign up to set email alerts
|

Protective and Curative Effects of Trichoderma asperelloides Ta41 on Tomato Root Rot Caused by Rhizoctonia solani Rs33

Abstract: Two molecularly identified tomato isolates, Trichoderma asperelloides Ta41 and Rhizoctonia solani Rs33, were characterized and antagonistically evaluated. The dual culture technique showed that Ta41 had a high antagonistic activity of 83.33%, while a light microscope bioassay demonstrated that the Ta41 isolate over-parasitized the pathogen completely. Under greenhouse conditions, the application of Ta41 was able to promote tomato plant growth and had a significant increase in plant height, root length, and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 78 publications
3
46
0
1
Order By: Relevance
“…Several authors have shown that the application of Trichoderma spp. was associated with an increase in root length, shoot length, and dry weight compared to the control plants [ 9 , 54 , 55 , 56 ]. Generally, the severe morphological and physiological changes including mosaic symptoms that occur upon viral infection are linked to changes in chlorophyll content and result in reduced photosynthesis [ 21 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown that the application of Trichoderma spp. was associated with an increase in root length, shoot length, and dry weight compared to the control plants [ 9 , 54 , 55 , 56 ]. Generally, the severe morphological and physiological changes including mosaic symptoms that occur upon viral infection are linked to changes in chlorophyll content and result in reduced photosynthesis [ 21 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings imply that WRKY proteins, which are well-known PR gene activators, play a key role in chromatin modifications that enhance gene expression ( Mayo et al, 2016 ). PR gene expression, including enzymes, such as cellulases, glucanases, and chitinases, is engaged in direct control of R. solani and plant biochemical barrier reinforcement ( Heflish et al, 2021 ). In another study, the interaction of bean plants with R. solani resulted in the downregulation of seven defense-related genes, including chitinases ( CH5b , CH1 ), PR1 , PR2 , PR3 , PR4 , and PAL , as a mechanism to overcome the plant defense response, allowing the infection process to progress within the plant.…”
Section: Role Of Mamps Reactive Oxygen and Nitrogen Species Transcrip...mentioning
confidence: 99%
“…Furthermore, PR-1 is a marker of the SA signaling pathway that inhibits programmed cell death, stimulates plant immunity, regulates SAR in plants, and may serve as a marker for early plant defense responses [87,88]. The accumulation and expression of PR-1 is associated with the activation of SA in response to pathogens [89]. In the present study, both treatments (p treatments < 0.0001) and time post-inoculation (p times < 0.0001) significantly affected the relative expression levels of PR-1.…”
Section: Pathogenesis-related Protein 1 (Pr-1)mentioning
confidence: 99%